A cohort study using pulmonary function tests and x-ray examination in toner-handling workers: Cross-sectional and longitudinal analyses from 2003 to 2008. (April 2015) - Kitamura, H; Terunuma, N; Kurosaki, S; Hata, K; Masuda, M; Kochi, T; Yanagi, N; Murase, T; Ogami, A; Higashi, T
Objectives: This study uses pulmonary function tests and chest x-ray examinations to examine the relationship between toner-handling work and its health effects. Methods: The subjects were 1504 male workers in a Japanese toner and photocopier manufacturing company, in the age range from 19 to 50 years in 2003. Personal exposure measurements, pulmonary function tests, chest x-ray examinations, biomarker measurements, and a questionnaire about respiratory symptoms were conducted. The present study reports the results of pulmonary function tests and chest x-ray examinations conducted in the subjects, which includes a cross-sectional study on the toner handling and non-handling workers and a longitudinal study from 2003 to 2008. Results: Few significant findings were suspected to be caused by toner exposure found in pulmonary function indices in both the cross-sectional and longitudinal studies. Any obvious fibrotic findings in chest x-ray findings related to the toner exposure could not be found out. Conclusion: No evidence of adverse effects on pulmonary function indices and chest x-rays was present in the toner-handling workers as compared to the nonspecifically exposed workers. Although the toner exposure concentration is quite low in the current well-controlled working environment, even among the toner-handling workers, we would like to continue this study in the future to verify the toner exposure health effects.